Simultaneous tracking of multiple whales using two fiber-optic cables in the Arctic - Rørstadbotnen, Robin André; Eidsvik, Jo; Bouffaut, Léa; Landrø, Martin; Potter, John; Taweesintananon, Kittinat; Johansen, Ståle; Storevik, Frode; Jacobsen, Joacim; Schjelderup, Olaf; Wienecke, Susann; Johansen, Tor Arne; et al. (Frontiers in Marine Science, 2023)
We demonstrate the use of fiber-optic cables in the Arctic to simultaneously track multiple whales over several hours along tens of km of cable length. Due to increased sea-ice melt in the Arctic, shipping and whale migration routes have changed. This calls for additional systems that can help locate whales in near-real-time to avoid fatal ship strikes in species-rich areas such as this. We used two fiber cables offshore Svalbard to simultaneously estimate the locations of up to eight whales over several hours, distributed around 60km of cable. Two independent methods estimated the locations; a brute force grid search and a Bayesian filter, based on the first time of arrival from acoustic signals recorded by two interrogators in Longyearbyen, Svalbard, Norway. These two methods gave consistent and accurate results. We can see when and where the various whales vocalized. Moreover, a dedicated field test using a small single air gun fired at known positions close to the two fibers allowed us to estimate the errors of the two localization methods to be 100 m. This error is characteristic of the air gun and the whale vocalizations as they have similar spatio-temporal properties. A significant contribution to this error likely arises from uncertainties in the position of the cables. Using these methods on two fiber-optic cables allow us to simultaneously track whales over 100 km of cable, within the constraints of increasing noise floor with range and coupling of the cable to the sea-floor and overlying water.